Impact of Nonmalignant Portal Vein Thrombosis in Transplant Recipients With Nonalcoholic Steatohepatitis. Issue 1 (4th January 2019) - Agbim, Uchenna; Jiang, Yu; Kedia, Satish K.; Singal, Ashwani K.; Ahmed, Aijaz; Bhamidimarri, Kalyan Ram; Bernstein, David E.; Harrison, Stephen A.; Younossi, Zobair M.; Satapathy, Sanjaya K.
Abstract : Nonalcoholic fatty liver disease is an increasingly prevalent condition, and its more severe progressive state, nonalcoholic steatohepatitis (NASH), is currently the second most common indication for wait‐listed adults in the United States. The association of portal vein thrombosis (PVT) prior to or at transplant and poor graft and patient outcomes is not well established, particularly among NASH patients who inherently have an increased hypercoagulable profile. Using the United Network for Organ Sharing data set, we analyzed graft and patient outcomes of patients transplanted for the indication of NASH with and without PVT. Of 3689 NASH transplant recipients, the prevalence of PVT was 12% (450 with PVT and 3239 without PVT). NASH transplant recipients with PVT had inferior graft and patient survival compared with NASH transplant recipients without PVT, even after adjusting for recipient and donor demographic characteristics, body mass index, synthetic dysfunction, and presence of diabetes. In a multivariate Cox regression model, NASH transplant recipients with PVT had a 37% increased risk of graft failure (hazard ratio [HR], 1.37; 95% confidence interval [CI], 1.15‐1.63; P < 0.001) and 31% increased risk of overall death (HR, 1.31; 95% CI, 1.09‐1.58; P < 0.001) compared with NASH transplant recipients without PVT at transplant. This difference in graft and patient survival was most pronounced in the early posttransplant period. These results demonstrate that NASH patients with PVT have decreased graft and patient survival independent of recipient and donor factors.